Application of Project Based Worksheet to Develop Students' Scientific Performance through Making Hand Cream from Black Rice Kefir - Delima, Dila; Windayani, Neneng; Aisyah, Riri; Sunarya, Risa Rahmawati; Sukmawardani, Yulia (Pusat Publikasi Ilmiah, STKIP Taman Siswa Bima, 2025)
This study aims to describe the learning process and analyze the development of students' scientific performance through the application of project-based worksheets in making hand cream from black rice kefir (Oryza sativa L.indica), as well as analyzing the characteristics of the hand cream products produced. The research was conducted at SMK MVP ARS International Bandung in class XI Pharmacy. The research approach used was quantitative with pre-experimental method and one shot case study design. The results showed that students' activities in the learning process reached a score of 93 and scientific performance obtained an average score of 89, both in the very good category. Product characterization showed that all formulations of hand cream from black rice kefir (Oryza sativa L.indica) met SNI standards with excellent quality based on pH, organoleptic, irritation, homogeneity, spreadability, and emulsion type parameters, and obtained a product assessment with an average score of 96. The LC50 value obtained from the antioxidant test results was 90.5500 (Strong). These findings indicate that the application of project-based worksheets is effective in developing students' scientific performance while producing quality products.